2018 Proceedings of the Twentieth Workshop on Algorithm Engineering and Experiments (ALENEX) 2018
DOI: 10.1137/1.9781611975055.7
|View full text |Cite
|
Sign up to set email alerts
|

A practical fpt algorithm for Flow Decomposition and transcript assembly

Abstract: The Flow Decomposition problem, which asks for the smallest set of weighted paths that "covers" a flow on a DAG, has recently been used as an important computational step in transcript assembly. We prove the problem is in FPT when parameterized by the number of paths by giving a practical linear fpt algorithm. Further, we implement and engineer a Flow Decomposition solver based on this algorithm, and evaluate its performance on RNA-sequence data. Crucially, our solver finds exact solutions while achieving runt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 16 publications
3
58
0
Order By: Relevance
“…Many approximation algorithms have been developed for finding a minimum path flow decomposition, e.g. [40,41], but these algorithms could not even handle our smallest data set (a mixture of 2 haplotypes of length 2500 bp). Therefore, we resort to other, more efficient means for obtaining a set of haplotypes from the given flow solution [42].…”
Section: Greedy Path Extractionmentioning
confidence: 99%
“…Many approximation algorithms have been developed for finding a minimum path flow decomposition, e.g. [40,41], but these algorithms could not even handle our smallest data set (a mixture of 2 haplotypes of length 2500 bp). Therefore, we resort to other, more efficient means for obtaining a set of haplotypes from the given flow solution [42].…”
Section: Greedy Path Extractionmentioning
confidence: 99%
“…Based on this reduction, in Section 3.2 we also propose a "bridge-reweighting" heuristic algorithm to solve the minimum FDSC problem. Additionally, we give an FPT algorithm for the minimum FDSC problem (Theorem 20), extending the one of Kloster et al [9]. Finally, in Section 4, to add to the complexity picture around the FDSC problem, we show that two application-oriented FD problems related to FDSC are NP-hard in the strong sense, even without requiring a solution with a minimum number of paths.…”
Section: Contributionsmentioning
confidence: 87%
“…In Kloster et al [9] it was shown that in the case of RNA transcripts, most of the time the "true" transcripts also provide a minimum flow decomposition of the splice graph. However, there can often be more than one solution to the minimum flow decomposition problem; indeed, Kloster et al found that, when the number of true transcripts is seven, the minimum flow decomposition found corresponds to the true paths in only 80% of the instances of that size, with lower accuracies as the number of true paths increases.…”
Section: Biological Settingmentioning
confidence: 99%
See 2 more Smart Citations